PERAN PERAWAT TERHADAP PELAYANAN KESEHATAN DI POLI UMUM DI PUSKESMAS TEPPO PATAMPANUA KABUPATEN PINRANG - Zaenal (Stikes Graha Edukasi Makassar, 2018)
Health care is a concept that is used in providing health services to the community. This research aims to know the role of nurses against health service in public health centers poly teppo patampanua Pinrang Regency. The type of research used descriptive research approach that is cross-sectional. A large population of 169 people while the number of samples that fill out questionnaires 45 people, sampling by means of accidental sampling. While the respondent conducted interviews 5 people. Data collected by questionnaire and interview against the subject, namely the community visiting Public Clinics Poly Teppo Patampanua, Kab. Pinrang. This research was conducted in week 2 and 3 April-May 2015. The results quantitatively demonstrates that: (a) the perception of the role of nurses as executor is good (80,79%), but the nurse on the item should determine the disease and provide treatment outcome is less good (48.9%). (b) the perception of the role of the nurse as educator is good (87,17%). Qualitative results showed the public perception of the role of health service users nursing in General is already good. The perception of the role of nurses as executor also had good will but they still assume the role nurses treat patients. Meanwhile, as their perception of the educator is also good